2015
DOI: 10.1007/s00436-015-4336-z
|View full text |Cite
|
Sign up to set email alerts
|

Mosquitocidal and antibacterial activity of green-synthesized silver nanoparticles from Aloe vera extracts: towards an effective tool against the malaria vector Anopheles stephensi?

Abstract: Mosquitoes represent an important threat for lives of millions of people worldwide, acting as vectors for devastating pathogens, such as malaria, yellow fever, dengue, and West Nile. In addition, pathogens and parasites polluting water also constitute a severe plague for populations of developing countries. Here, we investigated the mosquitocidal and antibacterial properties of Aloe vera leaf extract and silver nanoparticles synthesized using A. vera extract. Mosquitocidal properties were assessed in laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 211 publications
(91 citation statements)
references
References 55 publications
(52 reference statements)
8
82
0
1
Order By: Relevance
“…The appearance of the yellowish-brown color was an indication of the synthesis of colloidal AgNP in the medium. The dark color may be due to the excitation of surface plasmon vibrations, typical of the AgNP (Ahmad et al 2003;Dinesh et al 2015). In agreement with our results, a peak with maximum absorption at 410 nm characterized the synthesis of Aloe vera-fabricated AgNP , while peaks with maximum absorption at 450 and 420 nm were observed for Moringa oleifera-fabricated AgNP (Sujitha et al 2015) and Phyllanthus niruri-synthesized AgNP , respectively.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The appearance of the yellowish-brown color was an indication of the synthesis of colloidal AgNP in the medium. The dark color may be due to the excitation of surface plasmon vibrations, typical of the AgNP (Ahmad et al 2003;Dinesh et al 2015). In agreement with our results, a peak with maximum absorption at 410 nm characterized the synthesis of Aloe vera-fabricated AgNP , while peaks with maximum absorption at 450 and 420 nm were observed for Moringa oleifera-fabricated AgNP (Sujitha et al 2015) and Phyllanthus niruri-synthesized AgNP , respectively.…”
Section: Resultssupporting
confidence: 90%
“…Similarly, Devina Merin et al (2010) have reported the anti-bacterial activity of AgNP synthesized from marine microalgae. Dinesh et al (2015) focused on the antimicrobial activity of A. vera-synthesized AgNP tested at 300 ppm against three bacteria species. A. vera-fabricated AgNP led to zones of inhibition higher than 19 mm in all targeted bacteria.…”
Section: Anti-bacterial Activitymentioning
confidence: 99%
“…For both species, eggs were transferred to laboratory conditions [27 ± 2°C, 75-85 % R.H., 14:10 (L:D) photoperiod] and placed in 18 9 13 9 4 cm plastic containers containing 500 mL of tap water, waiting for larval hatching [44,45]. Larvae were reared in the containers and fed daily with a mixture of crushed dog biscuits (Pedigree, USA) and hydrolyzed yeast (Sigma-Aldrich, Germany) at a 3:1 ratio (w:w).…”
Section: Anopheles Stephensi Rearingmentioning
confidence: 99%
“…Larval food (0.5 mg) was provided for each tested concentration [44]. Control mosquitoes were exposed for 24 h to the corresponding concentration of the solvent.…”
Section: Acute Toxicity On Anopheles Stephensimentioning
confidence: 99%
See 1 more Smart Citation